2019
DOI: 10.1186/s12891-019-2954-9
|View full text |Cite
|
Sign up to set email alerts
|

Falls and fear of falling in older adults with total joint arthroplasty: a scoping review

Abstract: BackgroundPatients waiting or recovering from total joint arthroplasty (TJA) are at risk for falls which can lead to restriction of activity and negatively impact recovery. The objective of this scoping review is to critically appraise and synthesize the evidence in the reported number of falls, fear of falling, and risk factors associated with falls in older patients waiting for or recovering from TJA.MethodsSeven electronic databases were searched with no date limits and using language restriction (English).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
3
14
0
2
Order By: Relevance
“…We found that both ITW and control groups demonstrated significantly lower joint angles at loading, mid-stance, and push-off during toe walking (Table 1), suggesting rigidity at the lower extremity. The stiffening behavior and freezing the degree of freedom at the lower extremity joints could jeopardize gait stability and increase the chances of severe falls and injuries [40,41]. It was also found that foot segment angles at FIC were in the position of dorsiflexion for control typical walking, whereas it was at plantarflexion angle for cITW similar to toe walking (Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…We found that both ITW and control groups demonstrated significantly lower joint angles at loading, mid-stance, and push-off during toe walking (Table 1), suggesting rigidity at the lower extremity. The stiffening behavior and freezing the degree of freedom at the lower extremity joints could jeopardize gait stability and increase the chances of severe falls and injuries [40,41]. It was also found that foot segment angles at FIC were in the position of dorsiflexion for control typical walking, whereas it was at plantarflexion angle for cITW similar to toe walking (Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Bower et al [ 40 ] indicated that the fear of falling is high among these patients (61% 4 weeks post-fracture and 47% 12 weeks after) and therefore these PwD often cut back on activities and exercise routines, thus worsening their functional state. Balance impairment and mobility limitations are intrinsic factors of falls [ 41 ]. In fact, participants had a higher rate of falls one month after their discharge from hospital.…”
Section: Discussionmentioning
confidence: 99%
“…For balance confidence, this effect was even more pronounced. While FoF is more prevalent in frail older persons [ 13 ], the development of FoF is associated with multidimensional factors such as gender, age, and subjective health [ 64 ] as well as prior falls experience [ 65 ]. Therefore, gait parameters can only partly reflect these underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%